2012
DOI: 10.1111/j.1530-9134.2011.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Subperfect Game: Profitable Biases of NBA Referees

Abstract: This paper empirically investigates three hypotheses regarding biases of National Basketball Association referees. Identification of basketball referee bias is typically difficult as changes in observed statistics may be caused by either changes in referee bias or player behavior. We identify bias by exploiting the fact that referees have varying degrees of discretion over different types of a particular statistic-turnovers. This allows us to conduct a treatment and control-style analysis, using the less discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
60
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 18 publications
6
60
1
Order By: Relevance
“…Similarly, WNBA games that are broadcast on both national and local television networks generate greater outcome uncertainty, as the coefficient of about −1.7 from Models 1 and 2 in Table 4 indicate. These results for National2 and National23 support and augment the referee bias hypothesis described here and in Groot (2009), Price et al (2012 and Evans et al (2013).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, WNBA games that are broadcast on both national and local television networks generate greater outcome uncertainty, as the coefficient of about −1.7 from Models 1 and 2 in Table 4 indicate. These results for National2 and National23 support and augment the referee bias hypothesis described here and in Groot (2009), Price et al (2012 and Evans et al (2013).…”
supporting
confidence: 88%
“…Maintenance of product quality, or outcome uncertainty, is a function of relative team skills and referee bias, which is an important facet of this study. Given recent research by Groot (2009), Price, Remer, &Stone (2012) and Evans, Yewell, Caudill, &Mixon (2013) indicating how referee bias is useful to various sports leagues in creating greater outcome uncertainty, tests conducted in this study extend the work of these authors by providing links between referee bias, television coverage and outcome uncertainty in professional basketball leagues in the United States.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Sabotage on the part of athletes was for example reported by 3 Duggan and Levitt (2002), Garicano and Palacios-Huerta (2005), Dietl et al (2010), and Balafoutas et al (2012) among others. Unethical behavior was also found on the part of sports officials for example by Kocher (2004), Zitzewitz (2006), Parsons et al (2007), and Price et al (2007Price et al ( , 2009. Dietl et al (2009) showed that making officials aware of present unethical behavior helped to reduce the opportunities for unethical behavior.…”
Section: Introduction and Related Literaturementioning
confidence: 93%
“…For example, in an important paper on referee bias, Price, Remers, and Stone [11] examine profit-maximizing biases of referees in the National Basketball Association (NBA). They find that referees are likely to favor home teams, teams losing during games, and teams losing in playoff series.…”
Section: Introductionmentioning
confidence: 99%